KORELASI ANTARA VITALITAS PSIKIS DAN KOMPETENSI PSIKOMOTOR DENGAN KOMPETENSI KOGNITIF MATA PELAJARAN BIOLOGI SMA NEGERI 2 SRAGEN - MARLINA, ROHMI; Rosyidi, Alvi; Harlita, Harlita (Prodi Pendidikan Biologi FKIP UNS, 2006)
AbstractThis research was carried out upon the X grade student of SMA Negeri 2 Sragen. This research wereaimed to find the correlation between psychic vitality and cognitive, correlation between psychologicalcompetence and psychomotor competence with cognitive competence on biological learning and the dominantcontribution for each independent variable to cognitive competence on biological learning.This is a descriptive-quantitative research with ex post facto. The population of the study is the Xgrade of SMA Negeri 2 Sragen in academic year of 2004/2005. The sampling technique used is Simple RandomSampling. Sample was taken on 40 students within 8 classes. The data was then analyzed by using MultipleLinear Regretions.The result of research showed that there is positive correlation between psychologicat vitality andcognitive competence on biological learning of the X grade students of SMA Negeri 2 Sragen (r,ty = 0.424 withFstqtistic = 8'325 ) Ftabte (1,38; 0.0, = 4.10). Positive correlation was obtqin betyveen psychomotor competence andcognitivecompetenceonbiologicallearning(r,zy=0.346withF,so,;,,ir=5.163)Ftabte(1,38;0.0s)=4.10. Thereispositive correlation between psychological vitality and psychomotor competence with cogniti.ve competence onbiological learning (R = 0.5036 with F,r,;,,i, = 6.285 ) Ftabte (2,37;0.05) = 3.25). psychic vititity is the iidependentvariable giving a dominant cantribution to cognitive competence on biological with contribution of O2.St Vo.Keywords: Psychological vitality, psychomotor competence, cognitive competence